Fivefold Symmetric Photonic Quasi-Crystal Fiber for Dispersion Compensation from S- to L-Band and Optimized at 1.55 μm. (3rd August 2015) - Rajalingam, Sivacoumar; Alex, Zachariah C.
Abstract : A highly dispersive dual core quasi-periodic photonic crystal fiber is proposed for chromatic dispersion compensation. The dispersion for the dual concentric core fiber is optimized to compensate the chromatic dispersion with a high negative dispersion, accomplishing the communication bandwidth from S-band (1460 nm) to L-band (1625 nm). By precise control of structural parameter we have achieved a maximum dispersion of −18, 838 ps/nm-km with the phase matching wavelength centred around 1.55 μ m. We also numerically investigate the influence of structural parameter and doping effects and its response on peak dispersion parameter.